1996
DOI: 10.2135/cropsci1996.0011183x003600050049x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Elite Sorghum Inbred Lines Assessed with DNA Markers and Pedigree Information

Abstract: The amount of genetic diversity in parental lines of commercial sorghum [Sorghum bicolor (L.) Moench] hybrids is unknown, yet such comprehensive knowledge could improve the effectiveness of future hybrid development programs. Restriction fragment length polymorphisms (RFLPs) and pedigree data were used to investigate the genetic relationships in a group of 58 fertility restorer (R) and 47 sterility maintainer (B) elite sorghum inbred lines. The objectives of this study were to (i) assess the level of genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 0 publications
5
23
0
Order By: Relevance
“…Similar results were also observed in maize by (Melchinger et al, 1991;Messmer et al, 1992;Dubreuil et al, 1996) and barley (Melchinger et al, 1994). Likewise, cluster analysis (CA) of 148 US maize inbreeds (Dubreuil et al, 1996) as well as B-and R-lines in sorghum (Ahnert et al, 1996) and sunflower (Hongtrakul et al, 1997) partitioned the lines in accordance with their origin from different breeding groups and pedigree information.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar results were also observed in maize by (Melchinger et al, 1991;Messmer et al, 1992;Dubreuil et al, 1996) and barley (Melchinger et al, 1994). Likewise, cluster analysis (CA) of 148 US maize inbreeds (Dubreuil et al, 1996) as well as B-and R-lines in sorghum (Ahnert et al, 1996) and sunflower (Hongtrakul et al, 1997) partitioned the lines in accordance with their origin from different breeding groups and pedigree information.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, the traditional inter-group crossing approach utilized by public breeders may actually dilute potential heterotic patterns. The results reported by Ahnert et al (1996) also support this conclusion.…”
Section: Discussionsupporting
confidence: 69%
“…Various molecular genetic markers such as Restriction Fragment Length Polymorphism (RFLP) [11], Amplified Fragment Length Polymorphism (AFLP) [12], Inter Simple Sequence Repeats (ISSR) [13] and Simple sequence repeats (SSR) [14] were reported to be used in the molecular characterization of various plant genetic resources. Meanwhile, the SSR loci are reported to be highly polymorphic for the basic number of repeat units between species and especially among individuals within species and populations [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization based RFLPs (Restricted Fragment Length Polymorphism) markers were the first DNA marker system identified that could differentiate homozygote and heterozygote loci (Botstein et al, 1980). RFLP markers have been used for genetic variability studies in many different crops including in sorghum (Deu et al, 2006;Ahnert et al, 1996) and in maize (Pejic et al, 1998). The RFLP marker system is technically demanding, however, and found not to be suitable for high throughput and low cost screening.…”
Section: Sorghum Genetic Variability In a Global Contextmentioning
confidence: 99%
“…Molecular marker-based genetic distance groupings have increasingly been used in a number of crops including rice (Xie et al, 2014), triticale and in maize (Tracy and Chandler, 2006). In sorghum the most widely used grouping of inbred lines for F1 hybrid production is based on fertility restoration and maintainer status of the inbred parents, designated by R and A/B-line groups, respectively (Ahnert et al, 1996;Menz et al, 2004). These parental pools have been developed for production environments in temperate and subtropical zones where advanced and highly mechanized agricultural techniques are used (Jordan et al, 2003;Smith et al, 2010).…”
Section: Introductionmentioning
confidence: 99%